2010
DOI: 10.7209/tanso.2010.188
|View full text |Cite
|
Sign up to set email alerts
|

Ion-solvent interaction for lithium-ion transfer at the interface between carbonaceous thin-film electrode and electrolyte

Abstract: Lithium-ion batteries LIB have been used as power sources of portable electronic devices such as a laptop computer, a celler phone, and so on 1 , 2 . Moreover, LIBs have been expected as power sources of hybrid electric vehicle, plug-in hybrid electric vehicle, and electric vehicle due to their high energy densities.High rate performance, safety, and longer life of LIBs are required for practical use in these EVs. Among the above requirements, we have focused on the rate capabilities of carbonaceous negative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…[16] Based on this report, the activation energy in FEC-based electrolytes also seemed to be determined by the interaction between lithium-ion and FEC derived SEI. These results were consistent with the previous reports of graphite [14][15][16], which means the accuracy of calculating activation energies using these composite electrodes was enough. Figure 6 shows the CVs of CNS-2900 composite electrodes in 4 mol kg −1 NaTFSA/EC+DMC(1:1 by vol.)…”
Section: Lithium-ion Transfer Reaction At the Interface Between Gcns supporting
confidence: 92%
See 1 more Smart Citation
“…[16] Based on this report, the activation energy in FEC-based electrolytes also seemed to be determined by the interaction between lithium-ion and FEC derived SEI. These results were consistent with the previous reports of graphite [14][15][16], which means the accuracy of calculating activation energies using these composite electrodes was enough. Figure 6 shows the CVs of CNS-2900 composite electrodes in 4 mol kg −1 NaTFSA/EC+DMC(1:1 by vol.)…”
Section: Lithium-ion Transfer Reaction At the Interface Between Gcns supporting
confidence: 92%
“…The resistances of interfacial lithium-ion transfer are dominant in internal resistance of batteries at around the room temperature [13]. It was reported that the kinetics of lithium-ion transfer at the interface between negative electrodes and electrolyte solutions was influenced by the interaction between lithium-ion and solvents, counter anions or SEI in common organic electrolyte solutions, organic electrolyte solutions with film forming additives or bis(trifluoromethanesulfonyl)amide (TFSA) anion type ionic liquid based electrolyte solutions, respectively [14][15][16]. This tendency is also confirmed for the interfacial lithium-ion transfer at the model interface between solid electrolytes and liquid electrolytes [17].…”
Section: Introductionmentioning
confidence: 99%
“…When the SEI resistance was negligible, the charge-transfer resistances were estimated using the equivalent circuit shown in Figure d. As a result, the activation energy in 0.9 mol kg –1 LiTFSA/EC + DMC (1:1 by vol) was 56 kJ mol –1 , which was near to the reported values for highly oriented pyrolytic graphite (HOPG) and glassy carbon electrodes. , In the previous reports regarding the lithium-ion transfer resistances of carbon negative electrodes, the differences in activation energies of charge-transfer resistances measured in different electrolytes corresponded to the differences of interaction between lithium ions and solvents by calculating the heats of solvating reaction, and the rate-determining step was considered to be the final desolvation process . Based on the previous reports, solvents seem to be difficult to cointercalate into the bulk of low-crystallized carbons and desolvation process should be necessary for lithium-ion insertion into CNS-1100.…”
Section: Results and Discussionmentioning
confidence: 50%
“…To analyze each resistance inside batteries, electrochemical alternating current impedance spectroscopy is the specific tool because processes with different relaxation times can be divided by impedance spectroscopy . In LIBs, the interfacial lithium-ion transfer reaction at the interface between electrodes and electrolytes has been studied using electrochemical impedance spectroscopy. Based on these results, the interfacial lithium-ion transfer is especially the significant rate-determining step. The interfacial sodium-ion transfer at the interface between electrodes and electrolytes is also expected to be the significant step.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation